Cortisol as Biomarker for Stress, Depression, And Physical Activity Among Medical Student: A Systematic Review - Pratama, Yanasta Yudo; Rismayanthi, Cerika; Rahayu, Atikah (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
Cortisol is one of the most commonly used stress biomarkers. Stress and depression are increasing in young people, especially among college students, especially medical students. Physical activity has been recommended for stress and depression relief, but its effect on cortisol has not been confirmed. This study aims to analyze cortisol measurements for stress, depression, their physical activity among medical student. This literature search utilized PubMed and Google Scholar, combining the keywords